Subsurface Geological Structure and Geothermal System Modelling of Mount Bur Ni Telong, Indonesia, Based on Gravity Anomaly Interpretation - Marvita, Yurda; Santoso, Djoko; Alawiyah, Susanti; Marwan; Fadhli, Zul; Hapsari, Tika; Yanis, Muhammad; Ananda, Riski (Iraqi Journal of Science, 2026)
Mount Bur Ni Telong of Aceh, Indonesia, is a part of the Bukit Barisan volcanic arc region. It is located south of the young parasitic cone, Mount Bur Ni Geureudong. The Mount Bur Ni Telong area contains potential geothermal energy sources, as hot springs and fumaroles indicate. However, the information on Bur Ni Telong’s geothermal prospect is still limited. Therefore, this study aims to develop a subsurface structural model of the geothermal system using gravity data. The subsurface geological structure was determined using density calculations based on residual gravity anomalies, calculated using the moving average method. The 2D modelling results showed that the system is controlled by normal faults associated with hot spring activity at the surface. This section indicated that water from Mount Bur Ni Telong in the western part of the study areas infiltrates the subsurface, where it is heated and then flows upward as hot springs that emerge at the surface. Using this interpretation as an initial model of the geothermal system, the best prospect for development is a reservoir likely located northeast of the northwest–southeast-trending normal fault.